The Teachers’ Perceptions toward Students’ Disruptive Behaviors in the EFL Classroom at Primary Schools - Humaeroah, Humaeroah (Jurnal Bahasa Inggris, 2020)
This research describes students’ disruptive behaviors that occur in EFL classes, especially at primary schools. The objectives of the research are to find out (1) students’ disruptive behaviors that teachers perceive to be challenging at primary schools, (2) teachers’ perceptions about the causes of students’ disruptive behaviors at primary schools in Parepare, and (3) the effective ways to manage students’ disruptive behaviors at primary schools in Parepare. This research employed a descriptive qualitative research design. The participants of this research were English teachers at primary schools in Parepare. There were 10 English teachers from 10 primary schools in Parepare who were taken as informants in this research. The research findings show that (1) there are six categories of students’ disruptive behaviors that teachers perceive to be challenging in English classroom activities at primary schools. Those are saboteurs, non-participant students, physical aggression, bullying, over-exuberant students, and daydreaming;(2) it is also found that there are four causes of students’ disruptive behaviors in the EFL classrooms. Those are uncaring parents, level of the lesson, students’ psychological problems, cultural and linguistic barriers;(3) two effective ways applied by the teachers in the English classroom are encouragement from the teacher and development of a flexible teaching style. Some of the teachers also added that the effective ways that they applied were seating arrangement and student grouping.